On the cultivation of their community of practice: A case study of EFL Malaysian pre- service teachers - El Masry, Taghreed; Saad, Mohd Rashid Mohd (Nova Southeastern University, 2018)
This study examined the experiences of five EFL student teachers/pre-service teachers (PSTs) who participated in a Community of Practice (CoP) during their simulated teaching course and the practicum stage or teaching practice (TP), at The University of Malaya, a public Malaysian university. The experiences and tensions they encountered through this stage were discussed in the light of cultivating their CoP over five stages. Joining the CoP, increasing participation and negotiation of one’s tacit knowledge and assumptions were found to be productive at their learning to teach stage. However, some tensions, such as English proficiency level, self-confidence and agency, power relationships and worries of assessment persisted until the end of their practice. The results highlighted the significance of collaboration, reflection and social interactions with other CoP members as key to PSTs’ learning.